Privatization and 'destatization': school autonomy as the 'Anglo neoliberalization' of Irish education policy. Issue 2 (3rd April 2019) - Skerritt, Craig
Abstract : Symbolic of the rise of neoliberal principles in Irish education policy, there is now a move towards advancing school autonomy and decentralizing decision-making to individual schools, possibly emulating the academy model that has become widespread in England. Increasing the freedom and independence of schools may involve using private actors to provide what has traditionally been the service of the state, but it will most definitely involve schools behaving more like private sector organizations. While some of the new powers that would be devolved to schools might seem attractive, especially in how they are presented at an official level, this paper highlights how features of autonomous schools that may initially seem appealing are, in practice, likely to be unsuited to the Irish context. In this regard, this paper advises that school autonomy should not be advanced in Ireland.